Предмет: Алгебра,
автор: Николай1595
Упростить и написать ход решения и конечный ответ 8*(3*x+y)^2 -12*x*(6x+4y)
Ответы
Автор ответа:
0
8(3x+y)^2-12x(6x+4y)= 8(9x^2 + 6xy + y^2) - 72x^2 - 48xy = 72x^2 + 48xy +y^2 - 72x^2 - 48xy = y^2
Автор ответа:
0
8(3x+y)^2-12x(6x+4y)= 8(9x^2 + 6xy + y^2) - 72x^2 - 48xy = 72x^2 + 48xy +8y^2 - 72x^2 - 48xy =8 y^2 вроде всё)
Похожие вопросы
Предмет: Геометрия,
автор: hurliman1999
Предмет: Математика,
автор: tixonovairina1991
Предмет: Математика,
автор: kozlovamargarita2005
Предмет: Биология,
автор: ainura95
Предмет: Алгебра,
автор: alina12345987